Pengaruh Pemberian Probiotik Lactobacillus Pada Pakan Terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Mas (Cyprinus carpio) - Chika Clenecia Pakpahan; Suri Purnama Febri; Andika Putriningtias (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2026)
Common carp (Cyprinus carpio) is one of the most widely cultured freshwater fish species. The use of probiotics in feed is a potential strategy to improve fish growth and survival. This study aimed to evaluate the effect of dietary Lactobacillus probiotic supplementation on the growth performance and survival rate of common carp juveniles. A Completely Randomized Design (CRD) consisting of four treatments and three replicates was applied: P1 (control, without probiotic), P2 (10 mL/kg feed), P3 (15 mL/kg feed), and P4 (20 mL/kg feed). Juvenile common carp (4–5 cm) were reared for 40 days at a stocking density of 10 fish per container. ANOVA results showed that Lactobacillus supplementation significantly affected (P<0.05) growth performance and survival rate. The best results were obtained in P4 (20 mL/kg feed), with absolute weight gain of 1.47±0.22 g, absolute length gain of 0.86±0.86 cm, specific growth rate of 1.91±0.19% day⁻¹, feed conversion ratio of 1.07±0.12, and survival rate of 83.33±5.77%. In conclusion, supplementation of Lactobacillus at 20 mL/kg feed improved the growth performance and survival of common carp juveniles.